Market Discipline Under A Politicised Multilateral Fiscal Rule - Lessons from the Stability and Growth Pact Debate - Matthias Bauer; Martin Zenker (Graduiertenkolleg 'Konstitutionelle Grundlagen globalisierter Finanzmärkte - Stabilität und Wandel', 2012)
Does a multilateral fiscal rule improve market discipline in a monetary union? This paper studies the impact of political events that systematically undermined the Stability and Growth Pact (SGP) on EMU sovereign default risk for the period 2001 to 2005. For various EMU member countries our findings suggest that credit risk did not increase in the SGP's early years in response to the political undermining of the Pact. Due to the existence of systematic volatility effects we conclude that from its beginning the Pact was not perceived as a credible institution by financial markets. Bond markets have not been the watchdogs the proponents of transparency enhancing fiscal rules frequently claim them to be. Investors did not anticipate any serious consequences arriving from political non-ownership of the Pact and corresponding fiscal leeway on national public finances in the euro zone back then. In this context, policymakers working on a reform of Europe's fiscal framework should abstain from enhancing multilateral fiscal rules lacking political ownership, including the reformed SGP and the new 'European Fiscal Compact'.
urn:nbn:de:gbv:27-20131126-095736-7
Keywords: E62; F55; C22; C58; 330; fiscal rules; market discipline; sovereign credit risk; GARCH; Europäischer Stabilitätsmechanismus; Neue politische Ökonomie; Finanzpolitik; Regelbindung; Öffentliche Anleihe; Kreditrisiko; Rentenmarkt; Eurozone; Eurozone